2015
DOI: 10.5897/ajb2014.14184
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Brazil nuts: A review

Abstract: Brazil nut is a seed with high nutritional value and of great economic importance to the Northern region of Brazil. In addition to enabling direct consumption, its nutritional potential enables the development of various products. Among its nutrients, emphasis is given to the amino acid-rich proteins, lipid content and selenium, which exhibits antioxidant properties. This review addresses the nutritional value and approaches different technologies applied in the Brazil nut products process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Os difratogramas foram confeccionados usando o programa Microcal Origin 6.0 e foram apresentados na seguinte ordem: amostra não tratada (Am.total); amostra desferrificada e saturada com magnésio (Mg) e posteriormente solvatada com etileno glicol (MgEG); amostra desferrificada e saturada com potássio, com leituras executadas à temperatura ambiente (K25) e, após aquecimento, nas temperaturas assinaladas (K110, K350 e K550). A interpretação dos difratogramas foi feita com base nas tabelas da base de dados do JCPDS-ICDD (ICDD, 2016). A grafia dos nomes dos minerais está de acordo com Branco (1987).…”
Section: Caracterização Mineralógica Do Solounclassified
See 1 more Smart Citation
“…Os difratogramas foram confeccionados usando o programa Microcal Origin 6.0 e foram apresentados na seguinte ordem: amostra não tratada (Am.total); amostra desferrificada e saturada com magnésio (Mg) e posteriormente solvatada com etileno glicol (MgEG); amostra desferrificada e saturada com potássio, com leituras executadas à temperatura ambiente (K25) e, após aquecimento, nas temperaturas assinaladas (K110, K350 e K550). A interpretação dos difratogramas foi feita com base nas tabelas da base de dados do JCPDS-ICDD (ICDD, 2016). A grafia dos nomes dos minerais está de acordo com Branco (1987).…”
Section: Caracterização Mineralógica Do Solounclassified
“…E reportaram que que árvores mais produtivas de castanheira contribuem na remoção de bases trocáveis, favorecendo a acidificação do solo. Entretanto, a castanheira-do-brasil mostrou-se extratora de cálcio, os autores evidenciaram a importância do manejo visando a reposição do nutriente, como, por exemplo, a restituição ao solo dos resíduos de poda e das cascas das amêndoas e dos ouriços da castanheira (KLUCZKOVSKI et al, 2015).…”
Section: Introductionunclassified
“…High concentrations of Se have, exceptionally, also been found in Brassica genus (broccoli, cabbage, cauliflower) and onions [23]. Brazil nuts and mushrooms have extremely high concentrations of this element [6,50].…”
Section: Selenium In Food and Dietary Intakementioning
confidence: 99%
“…Evidence has shown that the Brazil nut (a native food) is a good source of FA (mono and polyunsaturated) and selenium [20,21]. Therefore, this study presents a protocol to evaluate the hypothesis that ingesting Brazil nut during lactation can modify the nutritional profile of HM, increase its energy density and selenium content, and improve its lipid composition.…”
Section: Introduction / Backgroundmentioning
confidence: 99%